Hoisting the photovoltaic performance by photocharging and plasmonic effect via aminosilane‐protected silver/barium titanate for dye‐sensitized solar cells. (14th March 2022) - Shalini Devi, K. S.; Bhojanaa, K. B.; Pavithra, N.; Pandikumar, A.
Summary: Recently, oxide perovskites coupled with plasmonic metal nanoparticles have focused on improving the efficiency of dye‐sensitized solar cells. However, the corrosion of metal nanoparticles with electrolyte hinders the practical applications. The combination of oxide perovskites with plasmonic metal nanoparticles shielded by amino silicates will provide an alternate solution to the existing difficulties. In that note, BaTiO3 nanoparticles are synthesized using sol–gel method and designated as BTO, followed by mixing up with different aminosilicates bounded Ag nanoparticles by photochemical reduction method and used as a photoanode for DSSC. The observed results clearly confirms the increase in the number of amino groups from silanes tends show the decrease in the band gap with increment in the VOC is due to upward shift of conduction band edge. The enhanced photovoltaic performance has been exhibited by APTMS‐bounded Ag/BTO (AMBTO) is due to the presence of mono amine group in silicate, that helps in effective binding of Ag as well as the presence of ‐O‐Si‐O‐ prevents the corrosion of Ag from the electrolyte. This leads to increase in photocurrent of AMBTO‐based photoanode of DSSC on measuring its photovoltaic performance under full sunlight illumination (100 mW cm −2, AM 1.5 G). The maximum obtained JSC, VOC, FF, and power conversion efficiency offered by AMBTO were 13.43 mA cm −2, 0.77 V, 57.2%, and 5.88%, respectively. About 39% improvement has been observed in AMBTO compared to BTO photoanode‐based DSSC. Thus, AMBTO can be considered as a potential candidate for the photovoltaic applications. Abstract : Illustration of increase in JSC and VOC corresponds to plasmonic and photocharging effect by the presence of monoamino silicate‐bounded silver over barium titanate leads to increase in the efficiency and electron life time.